(untitled) (AmS-Skrifter, 2020)
From around 1450 to 1712 merchants from North German towns, especially Bremen and Hamburg, took ships to the Shetland Islands. They broke the rules of the Hanse with a view to buying fish from the Shetlanders, and gave them goods in exchange that they could not otherwise acquire. They played a vital part in Shetland’s economy, and their activities were regulated by local officials. From 1610, however, they received more and more attention from customs officers, who imposed heavy tolls and duties on them. Battered by those officials, and from the 1690s by privateers and the collapse of the Shetland economy, they hung on until the first decade of the new century. Disappearing, after 1707, they were replaced by enterprising Shetlanders as purchasers and exporters of the Shetlanders’ fish.